Contribution to the genus Platybaetis Müller-Liebenau, 1980 (Ephemeroptera: Baetidae) in India - Vasanth, M.; Kubendran, T.; Subramanian, K.a.; Gattolliat, J.-L.; Suttinun, C.; Limatemjen (Zootaxa, 2025)
We present the description of a new mayfly species, Platybaetis arunachalensis sp. nov., based on larval specimens collected from Arunachal Pradesh, India. Additionally, we provide the first complete description and a new record of Platybaetis uenoi Müller-Liebenau, 1980, based on recently collected larval specimens from Nagaland, India. This study includes taxonomic updates for the genus Platybaetis Müller-Liebenau, 1980 in India, along with a distribution map of Platybaetis species and ecological insights into their habitats. Our work enhances the understanding of Platybaetis diversity and distribution in India, contributing valuable information for future ecological and conservation studies.